HASIL EKSKAVASI SITUS MALANGSARI, BANYUWANGI: Â€ŒDATA BARU DOLMEN DI JAWA TIMURÂ€ - Kasnowihardjo, Gunadi (BRIN, 2017)
Generally in Indonesia and especially in Java, until now, in East Java dolmens are known to be found in, which is in Bondowoso and Besuki. Lately, it is known that dolmen are also found in the area of Banyuwangi Regency. One of the monuments from this megalithic tradition found in the area of PT. Perkebunan Nusantara XII Malangsari, Banyuwangi, East Java. Based on information from the local community it is estimated that the Malangsari plantation area is the Dolmen Tomb Site. Physically, construction of the dolmen in this area only has a few interference because it is buried between 50-60 cm and covered by a coffee plantation which owned by PT. Perkebunan Nusantara XII. However, some of the dolmens have been excavated by people looters. They were able to open the dolmen tomb simply by opening a stone without unpacking its construction. Dolmen that was found from the excavation at Petak D 55 Sidomaju Block, Afdeling Mulyosari, Malangsari, are still intact if it is seen physically and from the construction, but both the human remains and artifacts ware not found. It is a proof that this dolmen has been opened before. Nevertheless, Malangsari dolmen is a very interesting object to conduct research, because of its wide distribution area and there has not been done a comprehensive research for this object. In the future, this object is important to investigate, both for the development of archaeological research, as well as for the benefit of archaeological resource management in Indonesia.